A preliminary assessment of freshwater snails in selected barangays in aAlang- Alang, Leyte - Carlobos, Peter John C.; Varona, Gracia F. (2017)
The Leyte and Samar islands have no updated inventory in the biodistribution of its freshwater gastropod species. Moreover, no studies related to the taxonomy of all freshwater snails have been conducted in Alang- Alang, Leyte Thus, this study is aimed to survey the freshwater snails present in the municipality. Freshwater snails were collected in accessible collecting stations within selected barangays through intensive snail search and random ring sampling in March 2017.
A total of 6022 individual freshwater snails belonging to 14 species from 6 families were collected and identified in Alang- Alang, Leyte. Three families belonged to Subclass Caenogastropoda (Ampullaridae, Vivparidae, Thiaridae), while the other three belonged to Subclass Heterobranchia (Lymnaeidae, Physidae, Planorbidae). Melanoides tuberculata (Thiaridae) was the predominant freshwater snail species, making up to 42.74% of all individual snails. It was followed by Pomacea canaliculata (Ampullaridae) and Tarebia granifera (Thiaridae). All other snail species had significantly lower relative abundances. The snail species were found in lotic and lentic habitats with muddy and sandy substratum. Differences in snail composition was attributed to disturbance by humans and other animals. Snail density was influenced by vegetation, abundance of the predominating species, and frequent disturbance. Higher species richness and diversity values were observed in stations with high pH and low temperature. However, Alang- Alang had relatively lower diversity with Shannon- Weiner diversity index values ranging from 0.9382 to 1.299. The high abundances and densities of M. tuberculata, P. canaliculata, and T. granifera influenced the low diversity values across all stations due to their invasive nature.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.